El nivel de eficacia de la audiencia de conciliación y el de la audiencia única en el proceso laboral - Díaz Arce, Nérida Fiorella (2017)
The thesis entitled "The level of effectiveness of the conciliation hearing in the labor process" aims to inform the legal community and the public of the current situation of the conciliation hearing in the ordinary proceedings labor. However, the single hearing in the abbreviated process, during 2014 and 2015; whereas, at the single hearing, conciliation can be used as an alternative dispute resolution mechanism; the conciliation hearing, whose main objective is to conciliate, has become a procedural act whose celebration is performed only to comply with a formality legally established within the process of a process. Through the study of various factors, such as the total procedural in the Labor Courts of Trujillo, and in each of the Specialized Courts and Peace Labor Court, the conciliation indices in the ordinary and abbreviated labor processes, on elaboration of statistical graphs, study of national and comparative doctrine, and the application of the corresponding statistical methods; it has been determined that the level of effectiveness of the conciliation hearing is 12.43%; while the level of effectiveness of the single audience is 33.92%; that, at present, in the development of the labor process, the type of hearing, whether conciliation or single, significantly influences the effectiveness of the conciliation; since the possibility of reaching a conciliation increases by 262% if it is a single audience, and the effectiveness of the single audience is 3.62 times exceeded a conciliation hearing; even though, according to the provisions of Law No. 2949 with the principal objective of the conciliation hearing is to conciliate. Following the study of this phenomenon, it has been found that there is a significant difference between the level of effectiveness of the conciliation hearing and the level of effectiveness of the single audience; situation that forces us to ask ourselves if the structure of the labor process, as it is designed in the New Labor Procedural Law, is fulfilling its aims and objectives; and, in addition, it respects the principles of orality, immediacy, celerity and procedural economy that inspire the labor process. As a result of this study, the thematic dispersion of the Thesis is concerned, this one has been realized in three parts; the first one, concerning the methodological framework; the second one, which contains the theoretical framework, which is divided into three titles, the first is about conciliation and effectiveness; the second deals with procedural labor law; and, finally the third on comparative legislation in procedural labor law; the third part contains the results of the research carried out and the discussion of each one of them; concluding with the conclusions that we have reached in accordance with the general and specific objectives that we had proposed; as well as the recommendations made with the objective of solving the problem already explained